A short pragmatic tool for evaluating community engagement: Partnering for Health Improvement and Research Equity - Oetzel, John G.; Boursaw, Blake; Littledeer, Lenora; Kastelic, Sarah; Castro-Reyes, Page; Peña, Juan M.; Rodriguez Espinosa, Patricia; Sanchez-Youngman, Shannon; Belone, Lorenda; Wallerstein, Nina (Frontiers in Public Health, 2025)
BackgroundAs community-engaged research (CEnR), community-based participatory research (CBPR) and patient-engaged research (PEnR) have become increasingly recognized as valued research approaches in the last several decades, there is need for pragmatic and validated tools to assess effective partnering practices that contribute to health and health equity outcomes. This article reports on the co-creation of an actionable pragmatic survey, shortened from validated metrics of partnership practices and outcomes.MethodsWe pursued a triple aim of preserving content validity, psychometric properties, and importance to stakeholders of items, scales, and constructs from a previously validated measure of CBRP/CEnR processes and outcomes. There were six steps in the methods: (a) established validity and shortening objectives; (b) used a conceptual model to guide decisions; (c) preserved content validity and importance; (d) preserved psychometric properties; (e) justified the selection of items and scales; and (f) validated the short-form version. Twenty-one CBPR/CEnR experts (13 academic and 8 community partners) completed a survey and participated in two focus groups to identify content validity and importance of the original 93 items.ResultsThe survey and focus group process resulted in the creation of the 30-item Partnering for Health Improvement and Research Equity (PHIRE) survey. Confirmatory factor analysis and a structural equation model of the original data set resulted in the validation of eight higher-order scales with good internal consistency and structural relationships (TLI > 0.98 and SRMR < 0.02). A reworded version of the PHIRE was administered to an additional sample demonstrating good reliability and construct validity.ConclusionThis study demonstrates that the PHIRE is a reliable instrument with construct validity compared to the larger version from which it was derived. The PHIRE is a straightforward and easy-to-use tool, for a range of CBPR/CEnR projects, that can provide benefit to partnerships by identifying actionable changes to their partnering practices to reach their desired research and practical outcomes.